Hubungan Pengetahuan, Sikap, Pelatihan, Pengawasan Dengan Persepsi Tentang Penerapan SMK3 - Dina Lusiana Setyowati (Universitas Faletehan, 2018)
Based on Regulation of Government Regulation Number 50 Year 2012, Occupational Safety and Health Management System (SMK3) is part of company management system as a whole in the framework of risk control related to work activities to create safe, efficient and productive workplace. PT. PLN (Persero) Mahakam Sector has included the OSHMS in its corporate management system. However, there has not been any review and assessment to the extent how the workers give support to the OSHMS. This research aims to find out the factors which influence the perception of the workers toward the OSHMS. The design of this research was analytic survey with quantitative method and using cross sectional approach with the total sample are 47 workers. This research applied correlation test of chi square with 95% CI. The research findings showed that there was a correlation between knowledge (p =0.029), attitudes (p =0.002) and OSH training (p =0.028) and the perception toward the OSHMS. Supervision (p =0.109) didn’t have a correlation with the workers perception. Attitudes about OSH becomes the most influential factor in the perception of workers on OSHMS.